Problems of Refugees in the Novels of Neerja Madhav: नीरजा माधव के उपन्यासों में शरणार्थियों की समस्याएँ - Nama, Kalpana; Kapil, Geeta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The tradition of leaving one’s own country and seeking refuge in another has been observed in human history since ancient times. Every nation, whether large or small, has, while considering its political and social conditions, economic situation, and various other factors, granted asylum to citizens of other countries. Through her novels, Neerja Madhav has also presented her own conclusions on this subject. Abstract in Hindi Language: एक देश को छोड़कर दूसरे देश में शरण लेने की परम्परा मानव इतिहास में प्राचीन समय से देखी जा रही है। कोई भी राष्ट्र फिर चाहे वह बड़ा हो अथवा छोटा अपने देश की राजनैतिक, सामाजिक परिस्थितियों, आर्थिक स्थिति एवं विविध तत्वों को ध्यान में रखकर दूसरे देश के नागरिकों को शरण देता आया है। नीरजा माधव ने अपने उपन्यासों क¢ माध्यम से स्वयं भी एक निष्कर्ष दिया है। Keywords: शरणार्थी, निराश्रय, व्याख्यायित, विभीषिका, विक्षिप्तावस्था, तकबीर, खूँखार, कत्लगाह, त्रासदी, तालिम